2008
DOI: 10.1177/0021989408095236
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Archive: Historical Fiction, Counter-modernities, and Suchen Christine Lim's A Bit of Earth

Abstract: Historical fiction often serves to provide us with an opportunity to question the past as well as the identities that have crystallized around the archive. As an example of historical fiction, Suchen Christine Lim's A Bit of Earth depicts the emergence of anti-imperialist feeling, self-realization, and national consciousness in nineteenth-century Malaya, celebrating nationalist feeling as a commendable gesture beyond the self towards a larger sociality. The text invokes these sentiments to look for alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Twenty-first century scholarship on historical fiction has often focussed especially on the genre's capacity to trouble established historical narratives and mythologies in a politically progressive way, such as through queer and postcolonial interventions (e.g. Harris, 2017;Poon, 2008). Medievalist historical fictions are not exclusively the domain of whiteness: Jonathan Hsy, for example, has recently shown that Asian American and Black medievalisms develop narratives that also counter white hegemonic claims over the past (Hsy, 2021).…”
Section: Medievalism Historical Fiction and Racismmentioning
confidence: 99%
“…Twenty-first century scholarship on historical fiction has often focussed especially on the genre's capacity to trouble established historical narratives and mythologies in a politically progressive way, such as through queer and postcolonial interventions (e.g. Harris, 2017;Poon, 2008). Medievalist historical fictions are not exclusively the domain of whiteness: Jonathan Hsy, for example, has recently shown that Asian American and Black medievalisms develop narratives that also counter white hegemonic claims over the past (Hsy, 2021).…”
Section: Medievalism Historical Fiction and Racismmentioning
confidence: 99%
“…Poon regards Suchen Christine Lim's A Bit of Earth (1997) as intervening in "official history" by highlighting an event that went almost unrecorded, "literally a footnote in history". 11 Given the recent interest in William Yate, Slow Water cannot be read in quite these terms: Yate is not a figure overlooked or forgotten by mainstream history. 12 Nonetheless, the ways in which Slow Water presents the story of Yate are indicative of the novel's engagement with history, highlighting a history of sexuality that intersects with a history of colonialism and settlement.…”
mentioning
confidence: 99%